Time spent near VO2max during different cycling self-paced interval training protocols - Agnol, C. D.; Turnes, T.; De Lucas, R. D. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Cyclists may increase exercise intensity by prolonging exercise duration and/or shortening the recovery period during self-paced interval training, which could impact the time spent near VO2max. Thus, the main objective of this study was to compare the time spent near VO2max during 4 different self-paced interval training sessions.